A Detailed Karyological Investigation of three Endemic Cobitis Linnaeus, 1758 Species (Teleostei, Cobitidae) in Anatolia, Türkiye - Unal Karakus, Sevgi; Gaffaroğlu, Muhammet; Karasu Ayata, Muradiye; Knytl, Martin (Cytogenetic and genome research, 2024)
INTRODUCTION: Comparative cytogenetics is a vital approach for diagnosing chromosome abnormalities and identifying species-specific patterns. In this study, chromosomal analysis of three Anatolian endemic Cobitis species was performed: Cobitis bilseli, C. fahireae, and C. turcica. METHODS: Conventional cytogenetic techniques such as Giemsa staining, C-banding, and Ag-NOR staining were applied, followed by measurements of chromosome arm lengths including analysis of the measured data. RESULTS: The diploid chromosome number, 2n = 50, was determined for all three species. The karyotype formulas were as follows: four pairs of metacentric, 5 pairs of submetacentric, and 16 pairs of subtelo-telocentric chromosomes in C. bilseli; 11 pairs of metacentric, 7 pairs of submetacentric, and 7 pairs of subtelo-telocentric chromosomes in C. fahireae; and 4 pairs of metacentric, 4 pairs of submetacentric, and 17 pairs of subtelo-telocentric chromosomes in C. turcica. Dark C-bands were observed on the pericentromeres of nearly all chromosomes in C. bilseli and C. turcica, whereas light C-bands appeared on the pericentromeres of some chromosomes in C. fahireae. Silver-stained metaphases revealed signals on the short arm of a submetacentric chromosome pair in C. fahireae (each homologous chromosome carries one signal), while in C. bilseli and C. turcica, Ag-NOR signals were detected on the long arm of a single metacentric chromosome (only one homologous chromosome carries the signal, and the signal-carrying chromosome is the largest chromosome in the karyotype). CONCLUSION: This study provides new cytogenetic data consistent with the phylogenetic distances between the studied species, indicating that pericentric inversions and/or translocations govern the formation of Cobitis karyotypes. INTRODUCTION: Comparative cytogenetics is a vital approach for diagnosing chromosome abnormalities and identifying species-specific patterns. In this study, chromosomal analysis of three Anatolian endemic Cobitis species was performed: Cobitis bilseli, C. fahireae, and C. turcica. METHODS: Conventional cytogenetic techniques such as Giemsa staining, C-banding, and Ag-NOR staining were applied, followed by measurements of chromosome arm lengths including analysis of the measured data. RESULTS: The diploid chromosome number, 2n = 50, was determined for all three species. The karyotype formulas were as follows: four pairs of metacentric, 5 pairs of submetacentric, and 16 pairs of subtelo-telocentric chromosomes in C. bilseli; 11 pairs of metacentric, 7 pairs of submetacentric, and 7 pairs of subtelo-telocentric chromosomes in C. fahireae; and 4 pairs of metacentric, 4 pairs of submetacentric, and 17 pairs of subtelo-telocentric chromosomes in C. turcica. Dark C-bands were observed on the pericentromeres of nearly all chromosomes in C. bilseli and C. turcica, whereas light C-bands appeared on the pericentromeres of some chromosomes in C. fahireae. Silver-stained metaphases revealed signals on the short arm of a submetacentric chromosome pair in C. fahireae (each homologous chromosome carries one signal), while in C. bilseli and C. turcica, Ag-NOR signals were detected on the long arm of a single metacentric chromosome (only one homologous chromosome carries the signal, and the signal-carrying chromosome is the largest chromosome in the karyotype). CONCLUSION: This study provides new cytogenetic data consistent with the phylogenetic distances between the studied species, indicating that pericentric inversions and/or translocations govern the formation of Cobitis karyotypes.
Keywords: druhová specificita; Fish; Male; chromozomy; karyotypizace; Turkey; C-banding; Karyotyping; karyotyp; mužské pohlaví; Ag-NORs; Species Specificity; Chromosome Banding; Turecko; Animals; Chromosomes; Centromeric index; zvířata; pruhování chromozomů; Spined loach; Diploidy; diploidie; Karyotype